Biopoéticas para las biopolíticas El pensamiento literario latinoamericano ante la cuestión animal - Yelin, Julieta (Latin America Research Commons, 2020)
This book addresses the state of research that link literature and literary criticism recent Latin American women with the current of posthumanistic thinking. To do this, put test the notion of biopoetics, a device that aims to identify and analyze the procedures by which writing literary approaches the living. The hypothesis that backbones the chapters is that the thought Latin American literary, in its productive facet and in its critical aspect, it dialogues with the horizon current reflection on the policies of the life, and that he does it through experimentation in which bodies and affections are not only organizing centers of the narratives but also lenses, ethical and political perspectives about the present. The volume thus offers a transdisciplinary theoretical panorama and a set of critical interventions that feed on each other: in the imbrications between language and life an object is cut out, biopoetic writing Latin American, which in turn makes one think to theory.